(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents the results of studies on changes in the granulometric composition of irrigated bog-meadow soils formed in the territory of the Juydam massif of the city of Fergana. It has been proven that according to the content of physical clay (<0.01 mm) in the genetic horizons of bog-meadow soils, they belong to heavy loamy and light clays (46.6-62.5%). Bog-meadow soils are characterized by the predominance of dusty particles in mechanical composition.